The cytotoxic action of diphtheria toxin and its degradation in intact Vero cells are inhibited by bafilomycin A1, a specific inhibitor of vacuolar-type H(+)-ATPase. - Toshiyuki Umata; Yoshinori Moriyama; Masamitsu Futai; Eisuke Mekada (1990)
The role of vacuolar-type H(+)-ATPase (V-ATPase) in the cytotoxic action of diphtheria toxin (DT) was studied by using bafilomycin A1, a specific inhibitor of V-ATPase. Studies with acridine orange showed that the acidification of intracellular acidic compartments was inhibited strongly when Vero cells were treated with 500 nM bafilomycin A1, indicating that bafilomycin effectively inhibits V-ATPase when it is added to the culture medium. The toxicity of DT to Vero cells, which was determined by the inhibition of protein synthesis by DT, was inhibited partially by bafilomycin at 10 nM and inhibited completely at 500 nM. Therefore, V-ATPase is involved in the expression of the toxicity of DT. Studies using 125I-labeled DT showed that bafilomycin inhibited the degradation of internalized DT, indicating that V-ATPase is also involved in this step. Subcellular fractionation revealed that 125I-DT accumulated mainly in the endosome fraction, and not in the lysosome fraction, when the cells were incubated with 125I-DT in the presence of bafilomycin. Under the cell fractionation conditions similar to those used for the DT-treated cells, we determined the location of 125I-labeled epidermal growth factor in the degradation pathway. The result suggests that bafilomycin A1 does not inhibit the transport of epidermal growth factor to lysosome.